2023
DOI: 10.1017/jns.2022.108
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of vitamin D supplementation in reducing body mass index and lipid profile in healthy young adults in Colombia: a pilot randomised controlled clinical trial

Abstract: The objective of the present study was to evaluate the efficacy of oral administration of vitamin D supplementation in reducing BMI and lipid profile in adolescents and young adults from a cohort in Bucaramanga, Colombia. One hundred and one young adults were randomly assigned to one of two doses of vitamin D [1000 international units (IU) or 200 IU] administered daily for 15 weeks. The primary outcomes were serum 25(OH)D levels, BMI and lipid profile. The secondary outcomes were waist-hip ratio, skinfolds and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Another study found that vitamin D supplementation in healthy adolescent boys has positive impacts on serum vitamin D, lipid profile, and inflammatory biomarker in which there is a decrease of triglyceride (p = 0.001) levels and an increase of HDL (p = 0.021) levels (Yarparvar et al, 2020). In healthy young adults, cholecalciferol supplementation reduced LDL levels significantly (p = 0.030) (Serrano et al, 2023). Several other studies however, did not find a significant difference of lipid profiles in subjects given vitamin D3 supplementation, such as by Jorde et al which found no positive effect of vitamin D on glucose tolerance, blood pressure, or serum lipids in a study involving 438 overweight or obese subjects (Jorde et al, 2010).…”
Section: Resultsmentioning
confidence: 98%
“…Another study found that vitamin D supplementation in healthy adolescent boys has positive impacts on serum vitamin D, lipid profile, and inflammatory biomarker in which there is a decrease of triglyceride (p = 0.001) levels and an increase of HDL (p = 0.021) levels (Yarparvar et al, 2020). In healthy young adults, cholecalciferol supplementation reduced LDL levels significantly (p = 0.030) (Serrano et al, 2023). Several other studies however, did not find a significant difference of lipid profiles in subjects given vitamin D3 supplementation, such as by Jorde et al which found no positive effect of vitamin D on glucose tolerance, blood pressure, or serum lipids in a study involving 438 overweight or obese subjects (Jorde et al, 2010).…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, participants with a baseline BMI < 30 kg/m 2 are more likely to derive lipid profile improvements from vitamin D supplementation, especially on TG levels. Due to the fat-soluble nature of vitamin D, it is more likely to be sequestrated in adipose tissue ( 54 ). Thus, individuals with a lowerBMI may exhibit a higher concentration of 25 OHD serum level when administered the same dosage of vitamin D supplementation, compared to people with a higher BMI.…”
Section: Discussionmentioning
confidence: 99%
“…The classic effects of vitamin D are mediated by its active metabolite, 1,25-dihydroxy vitamin D, which enables the absorption of calcium in the intestines, maintenance of adequate phosphate levels for bone mineralization, bone growth, and remodeling 2 . The biological effects of vitamin D are regulated by vitamin D receptors present in other tissues that are not related to calcium metabolism 3 .…”
Section: Introductionmentioning
confidence: 99%